PUBLIC SPEAKING ANXIETY DURING ORAL PRESENTATION: FACTORS AFFECTING AND HOW STUDENTS OVERCOME IT - Tarbani, Hafidh Nurhaqqi; Utami, Praditya Putri; Santika, Tika (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Singaperbangsa Karawang, 2024)
The main focus in this research is to investigate the factors affecting public speaking anxiety among students during oral presentation and to explore students’ strategies to overcome public speaking anxiety. The participants in this this case study research are 2nd grade of senior high school students at Daruttaqwien Islamic Boarding School. This research utilizes observation and interview to explore more deeply about factors causing public speaking anxiety and students’ strategies to overcome it during oral presentation. The results of this research found that the students experienced various factors affecting public speaking anxiety such as lack of confidence, language factor, grammar factor, pronunciation factor, and peer factor. Meanwhile, the students’ strategies in overcoming public speaking anxiety were think positively, preparation, practice, and deal with audience. Hopefully, the results of this study can be helpful as a reference for students and teachers in order to aware about public speaking anxiety, so the approach for overcoming public speaking anxiety can be found simultaneously.